Nilai Sosial dalam Kumpulan Cerpen Jawa Pos Edisi Bulan Agustus 2023 - Fahrudin Fahrudin (Departement of Mathematics Education, 2024)
The behavior and actions of each individual become a characteristic of his personal identity. So that community groups certainly consist of various individuals who can provide their views and traditions of life to the environment in which they live. In this way, the characteristics of life in society become a form of the way of life they live which becomes a benchmark for good society. The values ​​reflected in a group of people and the traditions that develop apply within their region. Furthermore, the social values ​​studied in this research are: Spiritual values, which include various conceptions related to everything related to human spiritual needs, such as: a) Value of truth, b) Value of beauty, c) Moral value, d) Value religion contained in the short story Jawa Pos. The value of truth originates from human reason, especially what is closely related to something that is considered to be true or false in a collection of short stories. The value of beauty is focused on the element of feeling, related to pleasure in something, especially related to the desire for objects. Moral values ​​are a form of human behavior between assessing which actions are good or bad, in the social sphere. Religious Values ​​are values ​​that exist within a person, when a person worships God the Creator.